Femoral offset restoration affects the early outcome of revision in patients with periprosthetic femoral fractures of Vancouver B2 - a single-center retrospective cohort study - Lei Sun; Wenjing Song; Zhongyuan Zhang; Ziyao Xu; Mengshuai Sun; Guangling Gao; Hongjiang Jiang; Changjun Ju (BMC Musculoskeletal Disorders, 2023)
Abstract Background Femoral offset (FO) restoration plays an important role in improving the prognosis and quality of life of patients undergoing hip replacement. However, it is not given enough attention in revisions among patients with periprosthetic femoral fractures (PPFFs); instead, more attention is given to reduction, fixation of fractures and stabilizing prostheses. The primary objective of this study was to evaluate the effect of FO restoration on the function of the hip joint in revisions of patients with PPFF of Vancouver B2. Moreover, we studied whether there is a difference in FO restoration between modular and nonmodular stems. Methods A retrospective review of 20 patients with PPFF of Vancouver B2 revised with a tapered fluted modular titanium stem and 22 patients with PPFF of Vancouver B2 revised with a tapered fluted nonmodular titanium stem from 2016 to 2021 was conducted. Based on the difference between the FO of the affected side and that of the healthy side, 26 patients were allocated into Group A (difference ≤ 4 mm), and 16 patients were allocated into Group B (difference > 4 mm). The postoperative Harris Hip Score (HHS), range of motion of the hip joint, length of both lower limbs and dislocation were compared between Group A and Group B. The proportions of patients with FO restoration (difference ≤ 4 mm) and stem subsidence were compared between the modular and nonmodular groups. Results The mean follow-up time was 34.3 ± 17.3 months, and all cases achieved fracture healing at the last visit. Patients in Group A had a higher HHS, larger range of abduction, fewer dislocations and less limb length discrepancy (LLD). Patients in the modular group had a higher proportion of FO restoration and less subsidence. Conclusion FO restoration improves postoperative hip joint function and reduces dislocation and LLD in revisions of patients with PPFF of Vancouver B2. Compared with nonmodular prostheses, modular prostheses tend to be easier for FO restoration under complex circumstances.